Recent Developments of Directional Overcurrent Relay Coordination in Ring Distribution Network Based on Hybrid Optimization Techniques - Annas Alamshah; Suzana Pil Ramli; Nurulafiqah Nadzirah Mansor; Muhamad Usama; Hazlie Mokhlis; Hadi Suyono; Rini Nur Hasanah (IEEE Access)
As power distribution systems evolve from conventional radial structures to more complex ring networks, driven by the widespread integration of distributed generation (DG), the challenge of ensuring reliable and effective protection becomes increasingly critical. Directional Overcurrent Relays (DOCRs) are pivotal in this context, protect the network through precise coordination between primary and backup protection schemes. However, optimizing these settings is a daunting task due to the nonlinear nature of the problem and the myriad constraints involved. This paper embarks on a comprehensive exploration of cutting-edge optimization techniques deployed to tackle DOCR coordination challenges. The paper delves into Nature-Inspired Algorithms (NIAs), metaheuristic approaches, mathematical formulations, and artificial intelligence methods, critically assessing their capabilities in navigating the complex landscape of relay coordination. While NIAs excel in exploring vast search spaces, their slower convergence can be a drawback. Metaheuristics offer robust solutions but at the cost of high computational demand, and traditional mathematical methods, though precise, may fall short in dynamic environments. Pushing the boundaries of current methodologies, the paper investigates hybrid optimization techniques that fuse the strengths of multiple approaches. These hybrids show promise in transcending the limitations of individual methods, offering innovative solutions for optimizing relay coordination in increasingly intricate network configurations. Moreover, this paper sheds light on the profound impact of emerging energy technologies on existing protection frameworks, emphasizing the urgent need for adaptive strategies to ensure stable and reliable power delivery. Through this investigation, actionable insights and forward-thinking solutions are proposed to bolster the safety and resilience of modern distribution networks, positioning them to meet the demands of a rapidly transforming energy landscape.